The backbone of Europe health, diet, work and violence over two millennia - Steckel, Richard H. 1944-; Larsen, Clark Spencer 1952-; Roberts, Charlotte A. 1957-; Baten, Jörg 1965- (Cambridge studies in biological and evolutionary anthropology, 2019)
"Using human skeletal remains, this volume traces health, workload and violence in the European population over the past 2,000 years. Health was surprisingly good for people who lived during the early Medieval Period. The Plague of Justinian of the 6th century was ultimately beneficial for health because the smaller population had relatively more resources that contributed to better living conditions. Increasing population density and inequality in the following centuries imposed an unhealthy diet - poor in protein - on the European population. With the onset of the Little Ice Age in the late Middle Ages, a further health decline ensued, which was not reversed until the nineteenth century. While some aspects of health declined, other attributes improved. During the early modern period, interpersonal violence (outside of warfare) declined possibly because stronger states and institutions were able to enforce compromise and cooperation. European health over the past two millennia was hence multifaceted in nature"...